Titanium Base Abutments in Implant Prosthodontics: A Literature Review - Al-Thobity, Ahmad M. (European Journal of Dentistry, 2021)
Implant abutments are essential components in restoring dental implants. Titanium base abutments were introduced to overcome issues related to existing abutments, such as the unesthetic appearance of titanium abutments and the low fracture strength of ceramic abutments. This study aimed to comprehensively review studies addressing the mechanical and clinical behaviors of titanium base abutments. A search was performed on PubMed/MEDLINE, Web of Science, Google Scholar, and Scopus databases to find articles that were published in English until December 2020 and that addressed the review purpose. A total of 33 articles fulfilled the inclusion criteria and were included for data extraction and review. In vitro studies showed that titanium base abutments had high fracture strength, adequate retention values, particularly with resin cement, and good marginal and internal fit. Although the clinical assessment of titanium base abutments was limited, they showed comparable performance with conventional abutments in short-term evaluation, especially in the anterior and premolar areas. Titanium base abutments can be considered a feasible treatment option for restoring dental implants, but long-term clinical studies are required for a better assessment.
Keywords: abutment; review; titanium base; titanium insert